Digital Marketing and Sustainable Marketing to Create Competitive Advantage in SMEs: The Moderating Effect of Value Co-creation - Farid, Farid; Putra, Setiawan Mandala; Bachri, Syamsul; Sutomo, Maskuri (Jurnal Manajemen Bisnis, 2025)
Research aims: This investigation seeks to examine how the incorporation of digital marketing influences sustainable marketing orientation and competitive edge among small and medium enterprises in Palu City, while also investigating value co-creation's moderating function in enhancing this connection. Furthermore, this study endeavors to ascertain how sustainable marketing orientation directly affects competitive positioning within the digital marketing framework.Design/Methodology/Approach: This study uses quantitative methods. The sample size of this study is 120 with sample characteristics, namely having been operating for at least one year, being micro, small, or medium scale, and having used digital marketing strategies. The respondents were chosen through probability sampling methodology, specifically employing the simple random sampling approach, to guarantee that all registered SME segments have equal opportunity for selection. The research analysis employs Structural Equation Model-Partial Least Square (SEM-PLS) methodological approach.Research findings: Research findings show that digital marketing adoption influences sustainable marketing orientation and also influences competitive advantage. In addition, sustainable marketing orientation was found to influence competitive advantage. Finally, value co-creation can moderate the influence between digital marketing adoption and sustainable marketing orientation on competitive advantage.Theoretical Contribution/Originality: Empirical evidence substantiates the connection between digital marketing implementation and sustainable marketing orientation, demonstrating their combined impact on competitive advantage within SMEs. This investigation further extends scholarly knowledge by identifying value co-creation's moderating function in amplifying digital marketing adoption's effect on competitive advantage through sustainable marketing orientation mechanisms. These findings provide a new perspective on the importance of collaboration with customers in digital marketing to achieve sustainable competitive advantage.Practitioners/Policy Implications: This research guides SMEs on the importance of digital marketing adoption and collaboration with customers through value co-creation to strengthen sustainable marketing orientation and increase competitive advantage in the market.Research Limitations/Implications: This study only covers SMEs in certain regions, thus possibly limiting the generalization of the results to geographic contexts and certain types of businesses.